PRAKTIK AKUNTANSI BERBASIS KEARIFAN LOKAL PADA PERSEROAN TERBATAS XYZ CIREBON - Titi Lestari; Muchammad Najiich (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2026)
This study explores local wisdom-based accounting practices in medium-scale Limited Liability Companies (LLCs) across five industrial sectors in Cirebon, Indonesia. These businesses often prioritize trust, kinship, and cultural values over formal accounting standards like PSAK. Financial transactions are frequently recorded manually, verbally, or based on memory, reflecting a trust-based culture that resists strict documentation and auditing. The study employs a qualitative exploratory method through interviews and observations, revealing limited accounting literacy, cultural resistance, and inadequate institutional support as major barriers to adopting formal systems. While some companies are beginning to use digital tools, integration remains inconsistent. The research finds that although these informal practices foster internal trust, they hinder transparency, external audits, and access to financing. Ultimately, the study recommends a hybrid model that bridges local cultural values and formal accounting principles. Such an approach could enhance financial accountability and sustainability while preserving cultural identity. This research contributes to the development of a contextual accounting model suitable for culturally diverse economic environments.